Analysis of BMT Assyafi’iyah Berkah Nasional Financial Reports During the Covid 19 Pandemic - Azzahra Jihan; Adivia Humayra; Fandy Ahmad; Falikhatun (Prodi Ekonomi Syariah Universitas Majalengka, 2023)
Sharia savings and loans cooperative BMT Assyafi'iyah Berkah Nasional is a financial institution whose activities are to collect funds from members and channel them through the Islamic financial system. The source of these funds comes from and for members of the cooperative. With so many competitors and uncertainty in economic conditions in Indonesia, it affects the instability of the financial sector. Therefore, it is necessary to assess the financial performance of the Sharia savings and loans cooperative BMT Assyafi'iyah Berkah Nasional using an analysis of financial performance using a ratio analysis. This study uses calculations derived from financial statement data. Meanwhile, the analytical tools used in this study used ratio analysis which includes liquidity ratio, solvency ratio, and rentability ratio. Overall, this analysis has been carried out from 2020-2021 and has a fairly good ratio.